DEVELOPMENT OF PUPILS’ CREATIVITY&NBSP;BY MUSEUM EDUCATIONAL ACTIVITIES - Širiakovienė, Asta; Pocevičienė, Rasa (Acta Paedagogica Vilnensia, 2010)
One of the features of information society is that education takes place not only in the organized formal educational environment but also in informal natural different places. The potential possibilities of museum educational activities in development of pupils‘creativity are investigated in this article. Educational environment in museum is dynamic and creative area for different kind informational and learning activities. The aim of the article is to clear up the possibilities to develop creativity by the aim of educational activities in museums. The analysis of 72 primary school teachers‘opinion is presented in the article. The conclusion made on their analysis is that teachers give positive evaluation to museum educational activities in area of creativity development but at the same time they recognize that not all potential possibilities in this area are used. The same idea could be confirmed on the basis of content of fifty museum educational programmes analysis. The case of Siauliai „Ausros“museum has shown that there is differentiation among educational programmes. Majority of educational programmes are offered in area of ethnography, majority of activities in them are quite creative. But some educational programmes (in area of technics history and restoration) are not aimed at creativity development, there are no activities for pupils‘creativity development offered.